Analisa Penerapan Sistem Just In Time dalam Upaya Meningkatkan Efisiensi Biaya pada CV. Cahaya Ornament Glassfibre Reinforced Cement Sidoarjo - Yudhistira, Leo Ekananta (Jurnal Ilmiah Cendekia Akuntansi; Vol 9 No 4 (2024): OktoberDO - 10.32503/cendekiaakuntansi.v9i4.5757, 2024)
Abstract The Just In Time (JIT) method is a method or system in which the production process is carried out in accordance with consumer demand and market demand by reducing or even eliminating costs that are considered wasteful and making products to meet consumer needs must be done as efficiently as possible. In connection with the importance of implementing Just In Time in managing a company, this system can be applied to CV companies. Cahaya Ornament Glasfibre Reinforced Cement Sidoarjo so that it is cost efficient.   This research is a descriptive research with a quantitative approach. The purpose of this study was to determine the application of the Just In Time system in an effort to increase Cost Efficiency at CV.Cahaya Ornament Glassfibre Reinforced Cement Sidoarjo. Data collection techniques in this study were interviews, documentation and literature study. As for the data analysis method used in this study is the Just in Time method.   The results of this study indicate that the application of the just in time system makes costs efficient. This is shown in the amount of inventory costs that have been incurred by the company amounting to Rp. 338,295,000, - whereas with the implementation of the Just In Time system the total cost of inventory is Rp. 323,428,634, - so that the company can carry out a cost efficiency of 4.4%. Thus the company needs to implement a just in time system in order to obtain cost efficiency so as to obtain optimal profit. Keywords : Just in Time System, and Cost Efficiency.